MAZHAB SYAFI'I SEBAGAI PARADIGMA DALAM PEMIKIRAN DAN PENETAPAN HUKUM ISLAM DI INDONESIA - Anwar, Syaiful; bawazir, Fuad; Sakina, Rafika; Lukita, Mince; Hernata, Novan; Miranda, Miranda; Ridwan, Muannif (VARIA HUKUM, 2023)
AbstractThe Shafi'i school plays a significant role in the thinking and establishment of Islamic law in Indonesia. This article aims to analyze the existence of the Shafi'i School as a paradigm in the thinking and establishment of Islamic law in Indonesia. This research was conducted using a descriptive-analytical approach and referring to various literature sources and related empirical studies. The concepts and principles of the Shafi'i School are presented, including its history and development as well as the contributions of the Shafi'i scholars to Islamic legal thought. Apart from that, the differences between the Shafi'i School and other schools of thought are also studied, especially in the methodology of ijtihad and the approach to sources of Islamic law. This research also highlights the advantages and relevance of the Shafi'i School in the Indonesian context, including its influence in the establishment of Islamic law in this country. However, criticism and challenges to the Syafi’i Mazhab are also considered, such as the limitations of adaptation and the plurality of schools in Indonesia. In order to strengthen the role of the Shafi'i School, this article recommends efforts to understand and further research on the thinking and application of Islamic law based on the paradigm of the Shafi'i School in Indonesia. AbstrakMazhab Syafi'i memainkan peran penting dalam pemikiran dan pembentukan hukum Islam di Indonesia. Artikel ini bertujuan untuk menganalisis keberadaan Mazhab Syafi'i sebagai paradigma dalam pemikiran dan pendirian hukum Islam di Indonesia. Penelitian ini dilakukan dengan menggunakan pendekatan deskriptif-analitik dan mengacu pada berbagai sumber literatur dan studi empiris terkait. Dipaparkan konsep dan prinsip Mazhab Syafi'i, termasuk sejarah dan perkembangannya serta kontribusi para ulama Syafi'i terhadap pemikiran hukum Islam. Selain itu juga dipelajari perbedaan mazhab Syafi'i dengan mazhab lain, terutama dalam metodologi ijtihad dan pendekatan sumber hukum Islam. Penelitian ini juga menyoroti keunggulan dan relevansi Mazhab Syafi'i dalam konteks Indonesia, termasuk pengaruhnya dalam penegakan hukum Islam di negeri ini. Namun kritik dan tantangan terhadap Mazhab Syafi’i juga diperhatikan, seperti keterbatasan adaptasi dan pluralitas mazhab di Indonesia. Untuk memperkuat peran mazhab Syafi'i, artikel ini merekomendasikan upaya untuk memahami dan meneliti lebih lanjut pemikiran dan penerapan hukum Islam berdasarkan paradigma mazhab Syafi'i di Indonesia.